2021
DOI: 10.1038/s41598-021-93071-5
|View full text |Cite
|
Sign up to set email alerts
|

Joint DNA-based disaster victim identification

Abstract: We address computational and statistical aspects of DNA-based identification of victims in the aftermath of disasters. Current methods and software for such identification typically consider each victim individually, leading to suboptimal power of identification and potential inconsistencies in the statistical summary of the evidence. We resolve these problems by performing joint identification of all victims, using the complete genetic data set. Individual identification probabilities, conditional on all avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In particular, for closed cases, Vigeland et al showed that identifying each UP individually can give inconsistent solutions and proposed a methodology that jointly considers all UPs [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for closed cases, Vigeland et al showed that identifying each UP individually can give inconsistent solutions and proposed a methodology that jointly considers all UPs [18].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, for closed cases, Vigeland et al showed that identifying each UP individually can give inconsistent solutions and proposed a methodology that jointly considers all UPs [18]. In all these cases, increasing the statistical power in hypothesis testing is imperative, which could require the incorporation of additional family members or genetic markers [2, 10, 19].…”
Section: Introductionmentioning
confidence: 99%